Chemical composition of potato tubers: the effect of cultivars and growth conditions - Leonel, Magali [UNESP]; do Carmo, Ezequiel Lopes; Fernandes, Adalton Mazetti [UNESP]; Soratto, Rogério Peres [UNESP]; Ebúrneo, Juliana Aparecida Marques [UNESP]; Garcia, Émerson Loli [UNESP]; dos Santos, Thaís Paes Rodrigues [UNESP] (Springer Nature, 2017)
The aim of the study involved evaluating the chemical composition of tubers of five potato cultivars that were grown under the same cultural practices in soils with low, medium, and high availability of phosphorus. The experimental designs corresponded to a randomized block with four replicates. Tuber samples were analyzed in terms of moisture, ash, protein, lipid, total sugar, fiber, starch, and phosphorus contents. The results suggested that increased availability of phosphorus in soil allowed the production of tubers with higher dry matter content, lower total sugar content, and a higher percentage of starch and protein. Hence, the aforementioned parameters constitute important factors corresponding to the nutritional and industrial quality of potatoes. Increased phosphorus availability in soil can promote significant changes in the composition of potato tubers, and thereby in potential uses of tubers.
Keywords: Nutrients; Soil fertility; Solanum tuberosum; Tuber quality